Introduction. Authoritarian resurgence: towards a unified analytical framework. (July 2019) - Cassani, Andrea; Tomini, Luca
Abstract: This introductory note to the Special Issue 'Autocracy Strikes Back: Authoritarian Resurgence in the Early 21st Century' situates this collection of articles in the burgeoning literature on authoritarian resurgence, and illustrates the conceptual terrain on which these articles make their contribution. In this regard, we discuss autocratization, authoritarian resilience, democratic transition failure, and autocracy-to-autocracy transition as processes of regime change representing different ways in which authoritarian resurgence may advance. Relatedly, we clarify how these processes of regime change differ from each other and provide a few basic coordinates to frame their comparative analysis.